Alternative lengthening of telomeres in normal mammalian somatic cells - Neumann, Axel A. (Cold Spring Harbor Laboratory Press, 2013)
Some cancers use alternative lengthening of telomeres (ALT), a mechanism whereby new telomeric DNA is synthesized from a DNA template. To determine whether normal mammalian tissues have ALT activity, we generated a mouse strain containing a DNA tag in a single telomere. We found that the tagged telomere was copied by other telomeres in somatic tissues but not the germline. The tagged telomere was also copied by other telomeres when introgressed into CAST/EiJ mice, which have telomeres more similar in length to those of humans. We conclude that ALT activity occurs in normal mouse somatic tissues.